ANALISIS FAKTOR PRODUKSI YANG MEMPENGARUHI PRODUKSI KOPRA DI KECAMATAN TOMOHON BARAT - Karouw Randy Alfredts Zwingly; Tommy F. Lolowang; Lyndon R. J. Pangemanan (Sam Ratulangi University, 2018)
This study aims to: (1) identify production factors that influence copra production and (2) analyze the elasticity of copra production factors from copra-producing farmers in West Tomohon District. This research was conducted from January to April 2017. The data used were primary data obtained by survey methods through direct observation and interviews with copra farmers. Data were analyzed using Cobb-Douglas production function. The results showed that (1) factors of production of planting area, plant population, outpouring of labor, amount of equipment, and experience used by copra-producing farmers in Tomohon Barat Sub-district jointly affected copra production but separately influential production factors real and positive for copra production, namely planting area, plant population, and outpouring of labor. Based on the scale of results which show increasing return to scale indicates that farmers are still able to obtain profitable production from a number of added production factors. (2) Based on the level of elasticity of production factors that are positive and more than one. This indicates that the use of planted area production factors, plant populations, and labor has not been efficient because it has not reached maximum profit. Each addition of the production factor resulted in an increase in copra production which continued to increase, while the use of production factors the number of equipment and experience showed a negative value indicating that the use of production factors is inefficient because the production will produce less copra even though the use of production factors is more. *jnkd*.